A bibliometric analysis of metonymy in SSCI-indexed research (2000–2023): retrospect and prospect - Sun, Yi; Lin, Mocheng (Frontiers in Psychology, 2025)
IntroductionMetonymy has gained increasing attention for its role in shaping language, thought, and communication. Despite its prominence, the thematic evolution and future directions of metonymy research remain underexplored. This study seeks to address this gap by analyzing metonymy research published between 2000 and 2023, providing a comprehensive overview of its key trends and emerging themes.MethodsA bibliometric analysis was conducted using data sourced from the Social Science Citation Index (SSCI) within the Web of Science Core Collection. Co-citation and co-word analysis were employed alongside k-means clustering techniques to identify research themes. Predictive modeling, including ARIMA and LSTM approaches, was used to forecast future research topics based on keyword trends.ResultsThe analysis identified 11 key research clusters, highlighting the central role of cognitive and conceptual linguistics in metonymy research, along with its applications in semantics, pragmatics, and multimodal contexts. Predictive modeling suggested the emergence of seven new research themes for 2024–2028, including the interaction between metonymy and discourse, its role in multimodal communication, and its application in social and cultural narratives.DiscussionThis study underscores the interdisciplinary nature of metonymy research, bridging linguistic, cognitive, and social dimensions. The findings highlight promising areas for future exploration, namely, its integration into digital communication and its impact on cultural identity construction. The methodological approach offers a robust framework for analyzing and predicting research trends, paving the way for innovative contributions to the field.